The Mannheim Dream questionnaire (MADRE): retest reliability, age and gender effects - Schredl, Michael (International journal of dream research, 2014)
Although dreaming is a genuinely subjective experience occurring in the inner world of the person while sleep ing there are quite a few aspects regarding dreaming that are worth being measured and investigated. Over the years several dream questionnaires have been developed but not often used very widely. The present questionnaire was de signed to elicit some form of dream history including dream recall, nightmares, lucid dreaming, attitude towards dreams, and the effects of dreams on waking life. Using an online questionnaire, a retest study was performed. The findings regarding the psychometric properties of the MADRE questionnaire seem very promising. One of the next steps will be to evaluate the English version of the MADRE and its application in different samples (e.g., nightmare sufferers, patients with sleep disorders and/or mental disorders) and different contexts (e.g., personality research) by research groups all over the world would be the best way to demonstrate the usefulness of this comprehensive dream questionnaire.